On the number of symbols that forces a transversal - Keevash, P; Yepremyan, L (Cambridge University Press, 2019)
Akbari and Alipour [1] conjectured that any Latin array of order n with at least n2/2 symbols contains a transversal. For large n, we confirm this conjecture, and moreover, we show that n399/200 symbols suffice.